Intelligent learning infrastructure for knowledge intensive organizations : a semantic web perspective - Lytras, Miltiadis D., 1973-; Naeve, Ambjorn (Hershey PA : Information Science Pub., 2006)
'This book discusses the convergence of knowledge and learning management and provides state-of-the art knowledge with a semantic web perspective' -- Provided by publisher.
Includes bibliographical references and index.
Keywords: Knowledge management; Organizational learning -- Management; Intelligent tutoring systems; Semantic Web